Vertical Stress Distribution at Soil Layers with Various Consistencies under the Footing Contact Area - Muhammad suradi Suradi; H. A. Hasanuddin; Nursamiah . (Lowland Technology International, 2021)
According to the Elastic Theory by Boussinesq, vertical stress distribution under the footing contact area will diminish with distance from the contact area and it is irrespective of the soil consistency. This study aimed at investigating the effect of the soil stratigraphy and consistency on vertical stress distribution at soil layers under the footing contact area. Soil investigation with CPT tests and relevant laboratory tests were carried out to obtain a reference of compressible soil layer thickness and relevant soil characteristics. The soil stratigraphy and parameters in conjunction with the vertical stress distribution were varied for two different types of soil, a typical granular soil e.g. sand and cohesive soil e.g. clay. Numerical analysis was performed to investigate the effect of the soil parameters on the vertical stress distribution. The results revealed a similarity between those obtained from the Elastic Theory (manual analysis) and numerical study using the PLAXIS software. However, the results of the numerical study showed a significant influence of the soil consistency on the vertical stress distribution at soil layers under the footing contact area.